Enhancing Critical Thinking Skills and Environmental Awareness through Problem-Based Learning: A Meta-Analytical Approach - Aripin, Nurul; Kurniati, Tuti; Festiyed, Festiyed; Asrizal, Asrizal; Diliarosta, Skunda; Helendra, Helendra (FKIP Universitas Lampung, 2024)
This study aims to analyze the influence of the Problem-Based Learning model on the development of students' critical thinking skills and environmental concern through meta-analysis research. Meta-analysis was carried out on 33 relevant national and international articles. Data collection was carried out through a systematic literature search on academic databases such as Sinta, Scopus, Web of Science, Google Scholar, and Eric Journal. Based on the results of the study, it showed an increase in the average pretest score of 67.09 to 80.98 on the posttest, as well as the size effect (ES) which ranged from 0.66 to 0.89. Data shows that the application of PBL is able to improve students' analytical thinking skills while fostering awareness of environmental issues. PBL, as an authentic problem-solving-based model, has a significant positive impact with consistent results at various levels of education, both secondary and tertiary. This study also identifies factors that support the success of PBL, such as learning design, the quality of interaction between students and teachers, and the relevance of the context of the problems presented. With an average error standard of ≈ 0.05, the results of this study have a high level of reliability. These results have important implications for the development of education policies to integrate the PBL model in the curriculum to improve students' critical thinking skills and environmental concerns. This study concludes that PBL is an effective learning strategy in shaping students who are not only intelligent, but also care about environmental sustainability. Keywords: meta-analysis, problem-based learning, critical thinking, environmental awareness.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1480-1497